2013
DOI: 10.1111/ipd.12076
|View full text |Cite
|
Sign up to set email alerts
|

Use of cone beam CT in children and young people in three United Kingdom dental hospitals

Abstract: When planning a CBCT service for children and young people, a limited FoV machine would be the appropriate choice for the majority of clinical requirements. It would facilitate clinical evaluation of scans, would limit the number of incidental findings and contribute to optimisation of radiation doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
60
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 17 publications
14
60
1
6
Order By: Relevance
“…It would be logical to concentrate on developing optimization strategies for the most common CBCT examinations performed in the most radio-sensitive age group. A recent survey by Hidalgo Rivas et al 47 showed that in a sample of UK Dental Hospitals, the most common CBCT examination in children and young people was for a localized region of interest in the anterior maxilla.…”
Section: Very Lowmentioning
confidence: 99%
“…It would be logical to concentrate on developing optimization strategies for the most common CBCT examinations performed in the most radio-sensitive age group. A recent survey by Hidalgo Rivas et al 47 showed that in a sample of UK Dental Hospitals, the most common CBCT examination in children and young people was for a localized region of interest in the anterior maxilla.…”
Section: Very Lowmentioning
confidence: 99%
“…Nonetheless, it is pivotal to keep exploring possibilities to reduce the dose further and to optimize it on an individual patient level according to the Bas low as reasonably achievable^(ALARA) principle [2]. A particular concern is the use of CBCT for paediatric applications [3], seeing that children are at a higher risk for radiationinduced cancer at a given dose [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…2 A recent hospital-based survey in the UK found that the most commonly performed dental CBCT examination in this age group was a localized examination of the anterior maxilla. 3 This was usually for assessment of impacted canine teeth in the context of possible resorption of incisors.…”
Section: Introductionmentioning
confidence: 99%